(3bWYI Yf JKHjJ fHhg eMeO Udi Gddg Ydjg hSdes - (3CHh WGdH jMji Hf GdMSjf Hf gGQhf GdgGQhfj,J (B404 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI bGd eG GdOdjd Ydi fHhg eMeO Udi Gddg Ydjg hSde bjd Gf GdOdGFd cKjQI Ydi Pdc s
(3BNQgG (B:s
(3aEPG QShd Gddg bGFe ai GdeSLO hgh jbhd CTgO Cf dG Edg EdG Gddg hCf eMeOkG QShd Gddg s
(3jdjgG eSCdI ai GdPHGFMs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs